THE USE OF TALK SHOW TECHNIQUE TO IMPROVE THE STUDENTS’ SPEAKING SKILL - Syariifah Faradiba Alattas; Nurdevi Bte Abdul; Muh. Arief Muhsin (FKIP Unismuh Makassar, 2021)
This research aimed to finding out the improvement of using talk show technique in speaking class eleventh grade students of SMA Muhammadiyah Limbung.In this research, the researcher applied pre experimental design to enhance the students speaking ability through talk show as technique in the classroom the Second Grades of Sma Muhammadiyah Limbung. The procedure of the treatment between the pretest (01) and the posttest (02). The pretest given to find out the students’ speaking ability before the treatment, and the posttest given to find out the students speaking skill after treatment. The population of this research was the students of the second grades SMA Muhammadiyah Limbung. The number of population is 120 students. In collecting data, the researcher used a test that consisted of pre-test, treatment, and post-test. The result of the research stated the using the Application of Tongue Twister to Improve the student’s pronunciation skill of the eleventh grade Students of SMA Negeri 4 takalar in academic 2020 it was proved by the t-test value that is 15.53 which was greater than the t-table value (2.074). The Eleventh Grade Students of SMA negeri 4 takalar had a high interest toward the use of The Application of Tongue Twister in Learning English Pronunciation. This was proved by the mean score .